Impact of Early Preclinical Exposure on Academic Performance, Clinical Skills, and Confidence Among BDS Students at Private Dental College - Sarah Ali; Shahzad Ahmad; Shazia Iqbal; Rakhi Issrani (Scientifica)
Conclusion: The implementation of early preclinical placements significantly enhanced academic achievement and professional development among BDS students. Integrating early clinical exposure into the dental curriculum enriches the overall educational experience and better prepares students for the demands of real-world dental practice.